Modelling the Relationship Between Offline and Online Communication Channels in Social Work With Traumatized People - Tsybulko, Lyudmyla; Ishutina, Olena; Chernetska, Yuliya; Roganov, Maxim; Kalchenko, Larysa (My University, 2024)
The article is devoted to exploring the possibilities of using online communication channels and modelling the relationship between offline and online channels in social work with traumatized people particularly those affected by the Chernobyl disaster. The distribution of age and number of Internet users for different categories of victims of the Chernobyl disaster has been calculated. It is shown that the percentage of Internet users, including the elderly ones, in foreign countries is higher than in Ukraine, which creates prerequisites for increasing their involvement in online communication. It is established that in the majority of scientific and educational information sources there is no grouping of the victims of the Chernobyl disaster into a separate category of the object of social work, which leads to the necessity of enriching the curricula of social workers’ professional training
Keywords: Online communication; mathematical model; social work; traumatized people; онлайн спілкування; математична модель; соціальна робота; травмовані люди